2002
DOI: 10.1519/1533-4287(2002)016<0645:rosttb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Strength Training to Body Image Among a Sample of Female University Students

Abstract: College women enrolled in a strength training class were evaluated before and after the class using a combination of physical fitness measures, including weight, percentage of body fat, body circumference, and strength measures. Forty-nine subjects participated in strength training, twice a week for a total of 12 weeks. At the end of the class, participants were asked to respond to 9 open-ended questions dealing with perceptions of body image. Physical results of the study showed a mean weight gain of 1 lb, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It is also unclear whether being in good physical condition (by being aerobically fit, physically active, and lean) is associated with body-shape dissatisfaction and perception. Some studies have shown that participants in aerobic dance and weight-training programs have positive body and self-image scores (Seggar, McCammon, & Cannon, 1988;Tucker & Maxwell, 1992;Ahmed, Hilton, & Pituch, 2002). However, it is unclear whether college-age women who are in good physical condition are more satisfied with bodyshape perception and less dissatisfied than those who are not in good physical condition.…”
mentioning
confidence: 99%
“…It is also unclear whether being in good physical condition (by being aerobically fit, physically active, and lean) is associated with body-shape dissatisfaction and perception. Some studies have shown that participants in aerobic dance and weight-training programs have positive body and self-image scores (Seggar, McCammon, & Cannon, 1988;Tucker & Maxwell, 1992;Ahmed, Hilton, & Pituch, 2002). However, it is unclear whether college-age women who are in good physical condition are more satisfied with bodyshape perception and less dissatisfied than those who are not in good physical condition.…”
mentioning
confidence: 99%
“…Body building might be used by female victims of maltreatment to cope with negative affect by physically empowering them or improving their body self-esteem (e.g. Ahmed et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that regular structured exercise will generate positive feelings about health and fitness (Stein & Motta, 1992;Tucker & Maxwell, 1992;McAuley, et al, 1997). Similarly, Ahmed, Hilton, and Pituch (2002) reported improved body-image following a regular structured exercise program, whereas Tucker and Mortell (1993) found evidence of improved physical self-concept in middle-aged women following exercise interventions. In other words, when individuals become more fit, they also tend to feel better about their overall appearance, possibly accentuated in American society in which youthfulness and fitness are values.…”
Section: Discussionmentioning
confidence: 99%